2022
DOI: 10.1126/sciadv.abl4644
|View full text |Cite
|
Sign up to set email alerts
|

Preneoplastic somatic mutations including MYD88 L265P in lymphoplasmacytic lymphoma

Abstract: Normal cell counterparts of solid and myeloid tumors accumulate mutations years before disease onset; whether this occurs in B lymphocytes before lymphoma remains uncertain. We sequenced multiple stages of the B lineage in elderly individuals and patients with lymphoplasmacytic lymphoma, a singular disease for studying lymphomagenesis because of the high prevalence of mutated MYD88 . We observed similar accumulation of random mutations in B lineages from both cohorts and unexpectedly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 89 publications
(132 reference statements)
0
29
2
Order By: Relevance
“…Moreover, MYD88 L265P is detected in more than 50% of IgM-MGUS patients, 10% of whom can evolve to WM and has been observed that those with a higher mutated allele burden (mutant allele relative to wild type) have a greater risk to progress to WM [40,77]. Of interest, MYD88 L265P by itself does not seem to have primary oncogenic effects, as has recently been demonstrated in mouse models [78][79][80].…”
Section: Referencementioning
confidence: 94%
“…Moreover, MYD88 L265P is detected in more than 50% of IgM-MGUS patients, 10% of whom can evolve to WM and has been observed that those with a higher mutated allele burden (mutant allele relative to wild type) have a greater risk to progress to WM [40,77]. Of interest, MYD88 L265P by itself does not seem to have primary oncogenic effects, as has recently been demonstrated in mouse models [78][79][80].…”
Section: Referencementioning
confidence: 94%
“…WM patients carry one or more somatic genetic mutations within malignant lymphoplasmacytoid cells (Figure 1), which have been reported to be present in less mature lymphoid and hematopoietic progenitor cells in some cases. 5 Whether common WM mutations can be detected in megakaryocytes and platelets remains an open research question. Understanding the WM genomic landscape is important, not only because specific mutations can influence disease presentation, and treatment options, 3,6 but also because they can potentially affect platelet function (see below).…”
Section: Molecular Basis Of Wmmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Of note, the MYD88 L265P transcript has also been detected in WM plasma cells, mature B lymphocytes, phenotypically normal B cell precursors and CD34 + haematopoietic precursor cells. 5 There are a number of other less common mutations now identified 14,15 and at least two distinct WM signature DNA methylation profiles specific for memory B cells or plasma cells. 16 Through association with Toll-like receptors (TLR) and the Interleukin-1 receptor (IL-1R), Myd88 has an important role in coordinating innate immune cell responses.…”
Section: Molecular Basis Of Wmmentioning
confidence: 99%
See 1 more Smart Citation
“…Treon et al performed whole-genome and Sanger sequencing in patients meeting the diagnostic criteria for WM, and identified MYD88 L265P as the most common somatic alteration in the lymphoplasmacytic cells [ 6 , 7 ]. It is worth noting MYD88 L265P is not specific to WM; a recent paper demonstrated the presence of MYD88 L265P in normal precursor and mature B lymphocytes from patients with lymphoma [ 8 ]. The authors concluded MYD88 L265P is a preneoplastic event and that additional genetic changes are required for lymphomagenesis.…”
Section: Introductionmentioning
confidence: 99%